Some Physiological Aspects of Development and Growth of Eucalyptus tereticornis SM (Syn Eucalyptus hybrid) - Guhathakurta, P. (Indian Forester, 1978)
Some of the physiological qualities of Eucalyptus tereticornis (Syn. E. hybrid) namely, that of reproduction and seeding, moisture relations, nutrition, etc., have been characterised in this paper. The propagation is carried out through seeds. Out crossing may be common, but it is also not self-incompatible. The time of flowering and innate genetical trait rule out outcrossing with every other species of the same genus. The impurity in Eucalyptus tereticornis seeds is considered mostly a mechanical mixture and hybridisation, if at all, is nominal. The germinative capacity cannot be rated high. Viability appears to be lost gradually. The important concern for seedlings and seeds in the nursery is the damping off disease attributed to excessive watering, high relative humidity and temperature and poor light. For planting, the desiccation of the nursery stock is prevented by putting them in the polythene containers. But root pruning Or knotting, as practised, tends to upset the internal water balance. This species develops root system rapidly. The species grows well in soils with good physical characteristics. The laterite or kankar pan limits root growth as also strong alkaline and saline conditions. The critical PH is UO. High water table causes inhibited root growth, chlorosis, poor crOwn development and paucity of leaves. The limit for soluble salt stands at 0.7%. The addition of organic matter results in greater growth. The effects of various macro nutrients on the growth are still uncertain, except tor organic C, N and P. It is more important to determine the levels of these fertilizers in mixture with one another for optimum results. E. tereticornis not as cosmopolitan as made out initially through it can grow in divergent habitats. Its physiological behaviour and requirements need a more correct assessment.